2008
DOI: 10.1016/j.ijpara.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-1-mediated glucose uptake protects human intestinal epithelial cells against Giardia duodenalis-induced apoptosis

Abstract: Infection with Giardia duodenalis is one of the most common causes of waterborne diarrheal disease worldwide. Mechanisms of pathogenesis and host response in giardiasis remain incompletely understood. Previous studies have shown that exposure to G. duodenalis products induce apoptosis in enterocytes. We recently discovered that sodium-dependent glucose cotransporter (SGLT)-1-mediated glucose uptake modulates enterocytic cell death induced by bacterial lipopolysaccharide. The aim of this study was to examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…A recent study reported a reduction in Caco-2 TER and an increase of paracellular flux after 0.3 µg/mL LPS treatment over a 5-day period. 29 Another study described a stable Caco-2 barrier after 50 µg/mL LPS treatment for 24 hours 30 as was also observed in our study, in which a stable TER was maintained over a 24-hour incubation period after incubation with 1 µg/mL LPS. These findings indicate that the incubation time might be a crucial factor in the outcome of barrier integrity after LPS challenge.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study reported a reduction in Caco-2 TER and an increase of paracellular flux after 0.3 µg/mL LPS treatment over a 5-day period. 29 Another study described a stable Caco-2 barrier after 50 µg/mL LPS treatment for 24 hours 30 as was also observed in our study, in which a stable TER was maintained over a 24-hour incubation period after incubation with 1 µg/mL LPS. These findings indicate that the incubation time might be a crucial factor in the outcome of barrier integrity after LPS challenge.…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports from our laboratory and others have demonstrated that G. duodenalis trophozoites induce pathophysiological events within intestinal epithelial cells (11,53,65,68,69). As these epithelial cells also participate in the induction of acute intestinal inflammatory responses by secreting chemokines such as CXCL8 (32-34), we investigated whether the attenuation of IL-1␤-induced CXCL8 secretion from CD small intestinal mucosal biopsy tissues implicated a G. duodenalis-mediated modulation of human intestinal epithelial CXCL8.…”
Section: Resultsmentioning
confidence: 94%
“…Initial experiments were performed to determine whether G. duodenalis NF trophozoites were capable of attenuating IL-1␤-induced CXCL8 secretion from human small intestinal mucosal biopsy tissues. This isolate has previously been used in our laboratory to characterize the pathophysiological effects of G. duodenalis infections (11,65). Adapting from previous studies (52), we developed a novel method of modeling G. duodenalis interactions with human small intestinal tissues, whereby human small intestinal mucosal biopsy tissues collected from the terminal ileum of patients with CD in remission were coincubated with live G. duodenalis trophozoites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46] The lumen-dwelling G. lamblia causes diffuse microvilli shortening, TJ disruption and epithelial cell apoptosis, 47,48 that may partly contribute to bacterial penetration. Moreover, it has been reported that intracellular C. jejuni-containing vacuoles deviate from the canonical endosomal pathways, avoiding delivery into lysosomes.…”
Section: Mechanisms Of Intestinal Bacterial Endocytosis By Epithelialmentioning
confidence: 99%